DEVELOPMENT OF A DC-DC CONVERTER FOR DC BUS VOLTAGE CONTROL OF SERIES CONNECTED DEVICE - Monteiro, T. C.; Galassi, M.; Terrazas, T. M. [UNESP]; Marafao, F. P. [UNESP]; Matakas, L.; Komatsu, W.; IEEE (Ieee, 2009)
The purpose of this work is to study voltage control and energy balance of a split DC bus topology within a power electronics equipment connected to the AC mains, such as UPS systems, wind power generators, active filters and FACTS devices. A typical configuration in such equipment has two mains connected converters sharing a common DC bus, one series connected and the other parallel connected. The DC bus is usually composed by a battery or a capacitor bank. In the proposed topology, the DC bus is divided in two sides, interconnected with a buck-boost converter, which controls power flow and DC voltage on both sides.
Keywords: buck-boost converter; DC bus voltage control